Persepsi dan perilaku ibu hamil dalam melakukan antenatal care (anc) pada masa pandemi covid-19 di kabupaten tabanan : Perception and behavior of pregnant women in antenatal care (anc) visits during the covid-19 pandemic in tabanan regency - Ni Wayan Sutarmi; DA Mirah Ardrini; Duarsa, Dyah Pradnyaparamita; Kurniati, Desak Putu Yuli (Bali Medika Jurnal, 2021)
In Indonesia, the number of Covid-19 cases in pregnant women is 3.9% and the prevalence of morbidity and mortality of pregnant women with Covid-19 is still unknown. However, several studies have shown that pregnant women may be very susceptible to Covid-19 infection so that it does little to cause fear and anxiety in pregnant women. Perceptions and behaviors of pregnant women need to be explored to see how health behavior is in making decisions for ANC visits. This study uses a qualitative method with an exploratory approach. Primary data were obtained through in-depth interviews with 12 pregnant women. The informants were pregnant women in Tabanan Regency who experienced an increase in the number of ANC visits at the Puskesmas. Data collection was carried out during January-February 2021. The data were analyzed thematically and presented using a narrative approach. Knowledge of pregnant women about the benefits of ANC and how to spread Covid-19 plays a very important role in the attitude of pregnant women in carrying out ANC. Adaptations in the application of health protocols continue to be carried out, this is because they feel vulnerable to being exposed to Covid-19. The feeling of fear and anxiety they felt did not stop them from doing ANC during the pandemic. The perception of severity is felt because of the experience of previous pregnancies, but the support and motivation makes pregnant women feel more able to avoid feelings of anxiety. ANC behavior of pregnant women can be seen in the selection of ANC locations that are felt to be safe and not crowded, such as Puskesmas and midwives. This study reveals that the anxiety of pregnant women during the Covid-10 pandemic can lead to levels of depression and anxiety if left untreated. There is a need for psychosocial support and information through online media for pregnant women during the Covid-19 pandemic. Keywords: perception, pregnant women, ANC, Covid-19